2021
DOI: 10.3390/jof7040279
|View full text |Cite
|
Sign up to set email alerts
|

Infections due to Rare Cryptococcus Species. A Literature Review

Abstract: Infections due to rare Cryptococcus species (other than C. neoformans species complex, C. gattii species complex, C. albidus or C. laurentii) are barely reported. The aim of this work is to present a comprehensive literature review of all the papers describing infections due to these species referenced in the main databases (PubMed/MEDLINE, ScienceDirect, Scopus, and Google Scholar). Clinical and epidemiological data together with laboratory findings (identification and antifungal susceptibility) of each isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Regarding the potential danger to human health, the most abundant fungi recorded in the caves have been considered opportunistic pathogens. They encompass Cladosporium cladosporioides [42], Beauveria bassiana [43], Parengyodontium album [44], Schyzophyllum commune [45], Aspergillus nidulans [46], Penicillium chrysogenum [47], in addition to basidiomycetous yeasts [48][49][50]. Jurado et al [51] reviewed the role of pathogenic and opportunistic microorganisms in caves and concluded that "the most-frequent diseases produced by cave microorganisms are located in the respiratory system and, therefore, it is recommended that visitors should, at the least, wear protective masks".…”
Section: Fungal Hazard In Show Cavesmentioning
confidence: 99%
“…Regarding the potential danger to human health, the most abundant fungi recorded in the caves have been considered opportunistic pathogens. They encompass Cladosporium cladosporioides [42], Beauveria bassiana [43], Parengyodontium album [44], Schyzophyllum commune [45], Aspergillus nidulans [46], Penicillium chrysogenum [47], in addition to basidiomycetous yeasts [48][49][50]. Jurado et al [51] reviewed the role of pathogenic and opportunistic microorganisms in caves and concluded that "the most-frequent diseases produced by cave microorganisms are located in the respiratory system and, therefore, it is recommended that visitors should, at the least, wear protective masks".…”
Section: Fungal Hazard In Show Cavesmentioning
confidence: 99%
“…Nevertheless, this study shows that the risk of exposure to highly pathogenic Cryptococcus species in nonurban human populations and bird caretakers is limited. For the less pathogenic RCFC species, particularly those already known to infect humans [ 5 ], the risk may be elevated in care personnel working in aviaries or wild fauna protection centers. The risk may also be present for peri/suburban human populations because residential gardens are attractive to some carrier birds, particularly Passeriformes.…”
Section: Discussionmentioning
confidence: 99%
“…They are followed by N. albida and P. laurentii , which account for 80% of non- neoformans/gattii cryptococcal infections. The remaining 20% of non- neoformans/gattii cryptococcal mycoses are due to 16 species of rare Cryptococcus and former Cryptococcus [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is responsible for one million infections per year among human immunodeficiency virus (HIV)-infected patients in the world; of these, approximately 625,000 die ( 15 ). Cryptococcus neoformans and Cryptococcus gattii are the most common and major pathogenic species complex in the genus Cryptococcus ( 16 ). C. gattii shares major virulence determinants with C. neoformans and was previously thought to be a subtype of C. neoformans , but genomic and transcriptomic studies revealed distinctions leading to recognize C. gattii as a unique species ( 17 ).…”
Section: Introductionmentioning
confidence: 99%